A data-driven investigation of successful local film profiles in the Indonesian box office - Budhi Sholeh Wibowo; Farizka Rubiana; Budi Hartono (Jurnal Manajemen Indonesia, 2022)
Many local film industries in developing economies are struggling to compete with foreign film hits. Surprisingly, despite the high exposure from imported films, the Indonesian film industry has maintained a robust domestic market in the last decade. This study aims to gather insights from this phenomenon by examining the key factors that distinguish the profiles of non-successful and successful local films at the Indonesian box office. The analysis was conducted based on the characteristics of 225 local films from 2017 to 2018. We employed a recent method to generate such profiles, namely the tree-based comparative analysis, which uses a machine learning model to augment the cross-case comparisons from a large pool of data. The study result suggests that the success of local films is mainly driven by the actor's popularity and the presence of foreign movie hits at the box office. Besides, we also found that the distinction between moderately successful and highly successful local films predominantly lies in story familiarity, suggesting the efficacy of the "brand extension" strategy in the Indonesian film industry. The study concludes by offering some managerial insights for producers and distributors to deliver successful films at the box office. Keywords— local film; Indonesian box office; success profiles; tree-based comparative analysis